The Influence of Green Supply Chain Management on Environmental Performance with Government Regulation as Mediation in Convection MSMEs - Alifurrohman Alifurrohman; Ina Siti Hasanah (University of Merdeka Malang, 2024)
Micro, small, and medium enterprises (MSMEs) are one of Indonesia's largest employment sources. According to the Ministry of Economy, Maritime Affairs and Investment, textile, convection, batik, yarn, and textile industries are among the MSME enterprises contributing to waste pollution in Indonesia. This study aims to determine the impact of Green Supply Chain Management (GSCM) incorporating government regulations on environmental performance in convection MSMEs in Bulak Timur Depok. This type of research is quantitative. The data sources used in this study are primary and secondary data. The research employed a questionnaire as the method for gathering data. The findings indicate a noteworthy impact of GSCM on environmental performance. Second, GSCM has a significant impact on government regulations. Third, government regulation does not have a substantial impact on environmental performance, and finally, government regulation does not have a significant impact on the mediation of GSCM on environmental performance.